KEPASTIAN HUKUM BAGI PEMENANG LELANG UNTUK DAPAT MENGUASAI OBJEK LELANG (Studi Pada: Grosse Risalah Lelang KPKNL Provinsi Lampung Nomor.044/20/2018) - Recca Ayu Hapsari; Ersa Marcellina (Jurnal Ilmiah Advokasi, 2022)
Auctions usually must be carried out in an open manner as a form of sales effort for goods or an object and must be carried out in public by using the bidding method at predetermined prices in written form or it can also be orally to get a fixed price. the highest authority in carrying out the auction in carrying out the auction mechanism who has the authority to make a legal deed in accordance with the current regulations, the auction official. Authentic Deed is one of the tools of proof that is so strong or ordinary what is meant by the term Risallah Auction and has a legal protection for the auction winner who will get legal protection related to the object that has been won in an auction. In the acquisition of the object and the right to the object, the winner of the auction has full rights to the object. Where the object is recognized by law. As well as the Accountability of the Auction Officer for the Process of Implementing the Mastery of the Auction.Keywords: Legal Protection; Auction; Auction Winner